Rapamycin Protects Against Peritendinous Fibrosis Through Activation of Autophagy - Wei Zheng; Yun Qian; Shuai Chen; Hongjiang Ruan; Cunyi Fan (Frontiers Media S.A., 2018)
Dysregulation of autophagy plays a pivotal role in fibrosis in multiple organs. However, the role of autophagy in peritendinous fibrosis is not well understood. Here, we hypothesize that autophagy plays a protective role in preventing adhesion formation. In a rat model of tendon injury, we observed dysregulated autophagy during excessive extracellular matrix deposition. Pharmacological induction of autophagy by rapamycin markedly alleviated the severity of peritendinous fibrosis in vivo. In NIH/3T3 fibroblasts and tenocytes, transforming growth factor β1 (TGF-β1) markedly activated myofibroblasts and increased collagen synthesis. Addition of rapamycin activated autophagy, reduced collagen synthesis, and suppressed myofibroblast activation. In vitro experiments also showed that rapamycin decreased cell proliferation and increased the number of cells arrested in G0/G1 phase. However, following pretreatment with the autophagy inhibitor 3-methyladenine (3-MA), rapamycin was unable to repress the fibrotic changes induced by TGF-β1. Autophagy related protein 5 (Atg5) RNA interference in fibroblasts also abolished the protective effects of rapamycin in vitro. In conclusion, our results point to rapamycin as a potential treatment strategy in the prevention of peritendinous fibrosis after tendon injury.